Arachnoid cyst of the cavum velum interpositum associated with cavum septum pellucidum and cavum vergae - Özdemir, Meltem; Dilli, Alper; Turan, Aynur; Soğukpınar Karaağaç, Seda (The European Research Journal, 2019)
A cavum velum interpositum is a normal variaton which is often detected incidentally in asymptomatic individuals. However, arachnoid cyst of the cavum velum interpositum is extremely rare and may cause symptoms similar to those of a third ventricular mass. On imaging, the main differentials of this cyst are; cystic dilatation of the cavum velum interpositum, cavum vergae cyst, arachnoid cyst of the quadrigeminal cistern, and epidermoid cyst. We present a case of an arachnoid cyst of the cavum velum interpositum coincidentally associated with the cavum septum pellusidum and cavum vergae. The cavum velum interpositum is a rare location for the arachnoid cysts. Accurate diagnosis of the arachnoid cysts of the cavum velum interpositum is important as they cause serious symptoms which can be reversed by surgical treatment.